Perancangan dan Analisis Pengaruh User Interface E-Learnig Terhadap Minat Belajar Siswa SMA/SMK Menggunakan Heuristic of Responsive Web Design - Angreyni Regal; Indrastanti R. Widiasari (APTIKOM SUMSEL, 2020)
During this current pandemic of Covid-19, online learning or online school is very important for high school students because they have not been allowed to going to school to take part in offline school as usual. The existence of E-Learning or Electronic Learning facilities will greatly help students to get material or theory in the form of lessons and information from the internet. As the Minister of Education emphasizes the implementation of online schools, more and more parents are beginning to facilitating their children with smartphones, so that students can join the online class or searching the subject on the internet. There are many online platforms that provide these things, one of which is the website. However, there are still many websites whose display or the user interface is not very attractive to students because their construction has not been designed properly and optimally. By using the Heuristic Of Responsive Web Design method as a benchmark to make this e-learning website, hoped that the website design and purpose will be fulfilled the need and expectations of students who want to find lessons material and want to learn by online.